Blockchain-based Decentralized Distribution Management in E-Journals - Agustin, Farida; Syafnidawati, Syafnidawati; Lestari Santoso, Nuke Puji; Amrikhasanah, Oktika Gita (Pandawan, 2020)
The application of blockchain in the context of E-Journal distribution to journalists is aimed at making the management paper adequately distributed and not misused. The security system in the distribution or management paper process of an open journal system is currently considered to be very lacking because one can duplicate the journal in an open journal system easily. Furthermore, it can be transferred to anyone who is not responsible. The security system in the distribution of an open journal system and the management of the management paper process is currently considered to be very lacking because one can duplicate the journal in an open journal system easily. Furthermore, it can be transferred to anyone who is not responsible. With the implementation of this blockchain technology, there are 3 (three) benefits, namely (1) The distribution of E-Journal in the Open Journal System is more targeted, and there are no errors. (2) The reputation of the Open Journal System becomes better with a sense of trust. This research will be implemented in an E-Journal in an Open Journal System using blockchain technology. (3) The management paper processing in the open journal system runs according to the procedure so that in the management process the distribution of soft copies and hard copies of the journal is protected from hacker threats, and this blockchain is used to guarantee its security.